Cognitive Improvement and Brain Changes after Real-Time Functional MRI Neurofeedback Training in Healthy Elderly and Prodromal Alzheimer’s Disease - Hohenfeld, Christian; Nellessen, Nils; Dogan, Imis; Kuhn, Hanna; Müller, Christine; Papa, Federica; Ketteler, Simon; Goebel, Rainer; Heinecke, Armin; Shah, N. Jon; Schulz, Jörg B.; Reske, Martina; et al. (Frontiers in Neurology, 2017)
Background: Cognitive decline is characteristic for Alzheimer's disease and also for healthy ageing. As a proof-of-concept study we examined whether this decline can be counteracted using real-time fMRI neurofeedback training. Visuo-spatial memory and the parahippocampal gyrus were targeted. Methods: Sixteen healthy elderly subjects (mean age 63.5 years, SD = 6.663) and ten patients with prodromal Alzheimer's disease (mean age 66.2 years, SD = 8.930) completed the experiment. Four additional healthy subjects formed a sham-feedback condition to validate the paradigm. The protocol spanned five examination days (T1–T5). T1 contained a neuropsychological pre-test, the encoding of a real-world footpath and an anatomical MRI scan of the brain. T2–T4 included the fMRI neurofeedback training paradigm, in which subjects learned to enhance activation of the left parahippocampal gyrus while recalling the path encoded on T1. At T5 the neuropsychological post-test and another anatomical MRI brain scan were performed. The neuropsychological battery included the Montreal Cognitive Assessment (MoCA); the Visual and Verbal Memory Test (VVM); subtests of the Wechsler Memory Scale (WMS); the Visual Patterns Test (VPT); and Trail Making Tests (TMT) A and B. Results: Healthy elderly and patients with prodromal Alzheimer's disease showed improved visuo-spatial memory performance after neurofeedback training. Healthy subjects also performed better in a working memory task (WMS backward digit-span) and in the MoCA. Both groups were able to elicit parahippocampal activation during training, but no significant changes in brain activation were found over the course of the training. However, Granger causality analysis revealed changes in cerebral connectivity over the course of the training, involving the parahippocampus and identifying the precuneus as main driver of activation in both groups. Voxel based morphometry showed increases in grey matter volumes in the precuneus and frontal cortex. Neither cognitive enhancements, nor parahippocampal activation were found in the control group undergoing sham-feedback. Conclusions: These findings suggest that cognitive decline, either related to prodromal Alzheimer's disease or healthy ageing, could be counteracted using fMRI-based neurofeedback. Future research needs to determine the potential of this method as a treatment tool.